The Effect Of Rewards And Punishment On Employee Work Motivation At PT Amanie International - Beti Sahdiya; Ida Ayu Made Er Meytha Gayatri; Zoniarti Zoniarti (Innovative Business Management Journal, 2026)
This study aims to determine the effect of rewards and punishments on employee work motivation at PT. Amanie Internasional. This study is motivated by the importance of a fair and consistent reward and punishment system in improving employee morale and discipline. The method used in this study is a quantitative method with a multiple linear regression analysis approach. Data were collected through questionnaires distributed to respondents who were employees of PT. Amanie Internasional, then analyzed using SPSS version 25.0 with validity and reliability tests, t-tests, F-tests, and the coefficient of determination (R²). The results showed that partially, the reward variable had a positive and significant effect on employee work motivation with a significance value of 0.013 < 0.05 and a t-value of 2.616 > 2.026. while the punishment variable also had a positive and significant effect with a significance value of 0.002 < 0.05 and a t-value of 3.408 > 2.026. Simultaneously, both variables had a significant effect on work motivation with an F-value of 20.476 > 3.25 and a significance value of 0.000 < 0.05. The coefficient of determination (R²) value of 0.525 indicates that 52.5% of employee work motivation variables can be explained by reward and punishment, while the remaining 47.5% is influenced by other factors outside this study. Thus, the implementation of a fair, transparent, and consistent reward and punishment system has been proven to increase employee work motivation at PT. Amanie Internasional.